Wrasse (Labridae) as cleaner fish in salmonid aquaculture – The Hardangerfjord as a case study - Anne Berit Skiftesvik; Geir Blom; Ann-Lisbeth Agnalt; Caroline M.F. Durif; Howard I. Browman; Reidun M. Bjelland; Lisbeth S. Harkestad; Eva Farestveit; Ole Ingar Paulsen; Merete Fauske; Trond Havelin; Knut Johnsen; et al. (Marine Biology Research, 2014)

Population characteristics of the world's northernmost stocks of European lobster (Homarus gammarus) in Tysfjord and Nordfolda, northern Norway - Ann‐Lisbeth Agnalt; Eva Farestveit; Kaare Gundersen; Knut E. Jørstad; Tore S. Kristiansen (New Zealand Journal of Marine and Freshwater Research, 2009)
The northernmost self‐sustaining populations of European lobster (Homarus gammarus) are found north of the Arctic Circle (66°33'N), in Tysfjord and Nordfolda, two large, deep, and relatively warm fjord systems in northern Norway. In contrast to most other Norwegian lobster populations, these genetically distinct populations are still found at relative high densities. This paper presents results from surveys conducted in the fjord systems in 1964–65 and between 1992 to 2005, and compares reproductive characteristics, morphology, growth, and catch‐per‐unit‐effort (CPUE). The lobster population in Stefjord, one of four individual fjords in the Tysfjord fjord system, was characterised by a small mean carapace length (CL, 78±11 mm SD), and less than 18% of the catches were larger than the minimum legal size of 88 mm CL. Growth rates were also low, with an average increment per moult of 4.0 ± 0.9 mm CL for females and 5.6 ± 2.1 mm for males. The crusher claw increased on average 5.5 ± 2.3 mm at each moult in females, and 11.2 ± 7.6 mm in males. The smallest ovigerous female was 62 mm CL, and more than 60% of females above 66 mm CL were berried (egg‐bearing). In contrast, lobster in the Nordfolda fjord system were larger, with more than 75% of the catch larger than minimum legal size, and the smallest ovigerous female was 76 mm CL. Males in Nordfolda increased on average 8.3 ± 2.4 mm in CL at each moult. Lobster populations in the area of the midnight sun (24‐h daylight during summer) were also morphologically different from lobster off southwestern Norway in crusher claw length for males and abdominal width for females. There were no differences in the size distribution or CPUE between the surveys in 1964–65 and between 1992 and 2005, leading to the conclusion that population density seemed to be relatively stable. The average density in the fjord systems of Tysfjord and Nordfolda was 155 ± 76 lobsters and average weight was 71 ± 26 kg per km shoreline in the main survey areas. The adaptation to a sub‐arctic environment has resulted in geneticlly distinct populations as well as slightly altered biology and behaviour. Our assessment suggests that the populations are vulnerable to exploitation, and conservation plans should be elaborated.

Allozyme variation in European lobster ( Homarus gammarus ) throughout its distribution range - Knut E. Jørstad; Eva Farestveit; Eamonn Kelly; Costas Triantaphyllidis (New Zealand Journal of Marine and Freshwater Research, 2005)
The European lobster, Homarus gammarus, is a high value species, which is widely distributed from the northern part of Norway to Morocco in North Africa. It is also found throughout the Mediterranean including the Aegean Sea. Knowledge of the genetic structure is necessary for rational management of exploited species. As part of a comprehensive genetic investigation of European lobster (EU‐project “Genetics of European Lobster”), 1514 lobsters from 14 locations were analysed for six polymorphic allozyme loci. Despite generally low levels of genetic differentiation (overall F ST = 0.016), the tests for population differentiation revealed highly significant values for all loci investigated. In particular, the lobsters from three areas including northern Norway, the Netherlands, and Aegean Sea in the Mediterranean were genetically different from lobsters from other regions. Lobsters from northern Norway have 30% of the genetic diversity observed in the samples from other areas, and polymorphism was only detected at the IDHP‐1* locus. A new slow‐moving allele at the GPI‐1* locus was found in the samples from the Aegean Sea. Pairwise F ST comparisons, as well as a UPGMA dendrogram based on Nei's genetic distance (calculated from allele frequencies across the six loci investigated), confirm the separate main groupings.

Sub-arctic Populations of European Lobster, Homarus gammarus, in Northern Norway - Knut E. Jørstad; Paulo A. Prodöhl; Ann-Lisbeth Agnalt; Maria Hughes; Apostolos P. Apostolidis; Alexandros Triantafyllidis; Eva Farestveit; Tore S. Kristiansen; John Mercer; Terje Svåsand (Environmental Biology of Fishes, 2004)